Facile preparation of poly(N-isopropylacrylamide)/graphene oxide nanocomposites for chemo-photothermal therapy. Issue 1 (31st December 2022) - Baipaywad, Phornsawat; Ryu, Naeun; Im, Soo-Seok; Lee, Ukjae; Son, Hyung Bin; Kim, Won Jong; Park, Hansoo
ABSTRACT: Carbon-based nanomaterials, such as carbon nanotubes, fullerenes, nanodiamonds, and graphene, have been investigated for various biomedical applications, including biological imaging, photothermal therapy, drug/gene delivery, cancer therapy, biosensors, and electrochemical sensors. Graphene oxide (GO) has unique physicochemical properties and can be used to restore conductivity through oxidation. In this study, we developed poly( N -isopropylacrylamide) (PNIPAM)-based nanogel systems containing GO for controlled in vitro drug delivery. The photothermal effects of the PNIPAM/GO- and PNIPAMAAM/GO-based nanogel systems were enhanced. The release of DOX from the PNIPAM/GO-based nanogel was achieved using the photothermal effect of near-infrared irradiation. Using a Cell Counting Kit-8 assay, the cytotoxicity of all conditions demonstrated that the PNIPAM composite-based nanogels were biocompatible with no significance.